Laboratory Detection and Gene Cassette Stability of the Novel Extended-Spectrum Beta-Lactamase, GES-2 from Pseudomonas aeruginosa - Dove, Mike G. (University of Pretoria, 2013)
Thesis (PhD (Medical Microbiology))--University of Pretoria, 2004.